2008
DOI: 10.1620/tjem.216.99
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Diastolic Dysfunction Is Associated with Cerebral White Matter Lesions in Elderly Patients with Risk Factors for Atherosclerosis

Abstract: Cerebral white matter lesions on magnetic resonance imaging (MRI) are considered to be the result of brain ischemic injury and a risk factor for clinical stroke. The purpose of this study was to elucidate the relationship between the cardiac diastolic function and cerebral white matter lesions in elderly patients with risk factors for atherosclerosis. The study subjects were 55 patients (75 ± 7 years) with risk factors for atherosclerosis including hypertension, diabetes mellitus, and dyslipidemia. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…It has been proposed that for SCIs, the cause lies in the low cerebral perfusion by reduced cardiac output in NVAF patients. 28,29 It has previously been reported that chronically low perfusion affects cerebral white matter lesions 30 and a higher rate of cerebral white matter lesions observed in atrial fibrillation accompanied by left ventricular hypertrophy has also been reported. 28 According to recent reports, the irregular heartbeat of atrial fibrillation gives rise to turbulence in the blood flow and damages the vascular endothelial cells, reducing production of nitric oxide, which has an antithrombotic effect.…”
Section: Discussionmentioning
confidence: 97%
“…It has been proposed that for SCIs, the cause lies in the low cerebral perfusion by reduced cardiac output in NVAF patients. 28,29 It has previously been reported that chronically low perfusion affects cerebral white matter lesions 30 and a higher rate of cerebral white matter lesions observed in atrial fibrillation accompanied by left ventricular hypertrophy has also been reported. 28 According to recent reports, the irregular heartbeat of atrial fibrillation gives rise to turbulence in the blood flow and damages the vascular endothelial cells, reducing production of nitric oxide, which has an antithrombotic effect.…”
Section: Discussionmentioning
confidence: 97%
“…Peak early (E´) and late (A´) diastolic mitral annular velocities and the ratio of early to late peak velocities (E´/A´) were measured over 3 cardiac cycles, and the results were averaged (Sohn et al 1997;Ommen et al 2000;Nikitin and Witte 2004). These parameters obtained from tissue Doppler echocardiography were also analyzed as parameters of LV diastolic function (Masugata et al 2008(Masugata et al , 2010. Furthermore, the ratio of E velocity to E´ velocity (E/E´) was calculated and was used as a parameter of LV diastolic dysfunction.…”
Section: Echocardiographic Examinationmentioning
confidence: 99%
“…No que se refere à hipótese de que a lesão cerebrovascular está associada às adaptações na função cardíaca 6,16 não foi confirmada no presente estudo, onde se verificou que a fração de ejeção, medida para expressar a integralidade da contração cardíaca e de extrema valia na apreciação objetiva da função ventricular sistólica, apresentou valores normais 20 , assim como constataram Masugata et al 30 . Porém, difere de McAreavey et al 18 que constataram que a alteração no enchimento do ventrículo esquerdo apresentou associação forte com o infarto cerebral em idosos após o AVE, e esta relação foi independente dos fatores de risco vasculares.…”
Section: Média ± Desvio Padrão Valores De Referênciaunclassified